EFFECT OF INSTRUCTIONAL STRATEGIES ON STUDENTS’ MORAL DEVELOPMENT - Ghani, Humaira; Kalsoom, Tahira; Khanam, Afifa; Kashif, Mahwish Fatima (International Journal of Psychosocial Rehabilitation, 2020)
The main objective of education system should be the accomplishment of knowledge and moral development of students. In modern age, moral crisis is rampant and educational institutions are facing the challenges regarding moral and behavioural issues. Pakistan’s schools, colleges and universities are also facing this danger and deterioration in morality can be observed in institutions. As for as curriculum and textbooks of syllabus are concerned, they are full of moral content, but students are not made involved in activities which could improve their moral reasoning. There has been no research on instructional strategies for students’ moral development in Pakistan’s educational institutions. Therefore, this study entitled as “Effect of Instructional Strategies on Students’ Moral Development”, was an attempt to fill such gaps. The exploratory research design was used for the study and to find out desired outcomes systematic literature review was done. It was found through systematic literature review that activities including role plays, class discussion, open ended question answers, moral dialogues and moral dilemmas, active participation and collaborative learning can be applied for moral development of students.